Person Centered and Trauma Informed Approach in Social Work Practice and Ways to Ensure Diversity in both Approaches - Niket Paudel (Asian Social Work Journal, 2021)
Person-Centered approach is an adapted work of Carl Rogers, where the focus was mainly on psychotherapy and counselling. Rogers believed, the basic nature of an individual is constructive and trustworthy – given that the individual is freely functioning. Person-Centered approach is the backbone of social work practice alongside trauma-informed approach. Any emotionally and physically daunting events that affects the response of an individual is trauma. Trauma damages the freely functioning state of an individual – emotionally, socially and behaviorally. By introducing an approach that is trauma-informed will help social worker to not only understand the emotions of the individual while working with them but also guide the social work practice in better understanding while working with the individuals.